Shack–Hartmann wavefront sensors based on 2D refractive lens arrays and super-resolution multi-contrast X-ray imaging; Journal of Synchrotron Radiation; Vol. 27, iss. 3 - Mikhaylov A. A. Andrey Anatoljevich; Reich S. Stefan; Zakharova M. A. Margarita Anatoljevna; Vlnieska V. Vitor; Laptev R. S. Roman Sergeevich; Plech A. Anton; Kunka D. M. Danays Morejon (2020, 2020)
Title screen